A Systematic Literature Review: Acrophobia Treatment with Virtual Reality - David Jose Giraldy; Wilson Novaldo (Bina Nusantara University, 2022)
Virtual Reality (VR) is becoming more popular as a treatment option for many phobias. We present a method that uses virtual reality in treatment to cure acrophobia in this research. Acrophobia is an anxiety condition that occurs when a person is exposed to heights. The goal of our study is to see whether Virtual Reality technology can be used to treat acrophobia. We conducted a comprehensive literature evaluation on publications relevant to acrophobia and virtual reality that were located on Google Scholar using a keyword-based search strategy. We noticed that the majority of papers involve more than two persons as a sample and use virtual reality exposure treatment. The participants' anxiety levels decrease with each exposure, suggesting that VR-based exposure might be employed as an acrophobic alternative treatment.